(untitled) (World Economics and Finance Bulletin, 2022)
The research sought to identify the results of the work of some Iraqi private banks and the net profit achieved, as well as measuring the relationship between the net profits of commercial and Islamic banks and the share prices of these banks, The problem of the study was summarized by asking about the contribution of the realized profits of the Iraqi commercial and Islamic banks to the stock prices, and to test the research hypothesis, which stipulated the existence of a statistically significant relationship between (net profit for Iraqi commercial and Islamic banks) and their stock prices, Standard quantitative methods were used on the data of the Economy Bank for Investment and Finance (commercial bank) and the Iraqi Islamic Bank (Islamic bank) in the period from 2006 to 2019, and the research concluded that it is important for banks to monitor the mechanisms for determining their stock prices in the Iraqi stock market. It is not spontaneous and is intended for trading purposes. The banks should not leave room for speculators to determine the share price, which necessarily affects the market value of the bank.